The genome sequence of the Gold Spot moth, Plusia festucae (Linnaeus, 1758) [version 1; peer review: 2 approved] - David Hill; Tom Prescott; Stuart Bence (Wellcome Open Research)
We present a genome assembly from an individual male specimen of Plusia festucae (Gold Spot; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence has a total length of 422.50 megabases. Most of the assembly (99.92%) is scaffolded into 31 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.3 kilobases in length. Gene annotation of this assembly on Ensembl identified 19,273 protein-coding genes.